2010
DOI: 10.1111/j.1440-0960.2010.00630.x
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoidosis with cutaneous granulomatous vasculitis

Abstract: Ulceration of non-caseating granulomas is a rare cutaneous presentation of sarcoidosis. Granulomatous vasculitis is classically associated with Wegener's granulomatosis, lymphomatoid granulomatosis or Churg-Strauss syndrome. It is also commonly noted in pulmonary sarcoidosis, but has seldom been reported in cutaneous sarcoidosis, particularly the ulcerative variant. We present a rare case of sarcoidosis with multiple purpuric leg ulcers showing a granulomatous vasculitis histologically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
23
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 14 publications
2
23
1
Order By: Relevance
“…The lung (57%) and lymph nodes (65%) are the two most commonly affected extra‐cutaneous organs, followed by the eye (43%). However, erythema nodosum was very uncommon in several studies of cutaneous sarcoidosis reported from Taiwanese and other Asian countries 11–17,19,22–31 . In the present study, no case of erythema nodosum was diagnosed.…”
Section: Discussioncontrasting
confidence: 58%
See 3 more Smart Citations
“…The lung (57%) and lymph nodes (65%) are the two most commonly affected extra‐cutaneous organs, followed by the eye (43%). However, erythema nodosum was very uncommon in several studies of cutaneous sarcoidosis reported from Taiwanese and other Asian countries 11–17,19,22–31 . In the present study, no case of erythema nodosum was diagnosed.…”
Section: Discussioncontrasting
confidence: 58%
“…Once considered rare in Taiwan, sarcoidosis has been increasingly diagnosed and reported in the last two decades 11,13–16,19,22–30 . About 331 Taiwanese cases (our 37 cases of the present series included), have been reported since 1960, mostly after 1992 11–16,19,22–30 . Of these, 107 cases were reported by dermatologists, 115 cases by ophthalmologists and 109 cases by internists.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Cutaneous sarcoidosis is known for its protean clinical presentations, including erythema nodosum, macules, papules and plaques, scar sarcoidosis, ichthyosis, Darier–Roussy lesions, alopecia and onychodystrophy 4 . Physicians should be aware of cutaneous signs of sarcoidosis because they lend themselves to biopsy facilitating diagnosis, many have prognostic significance, and they can impose a significant burden on quality of life 5 …”
mentioning
confidence: 99%